Time Series Analysis of Impact of Money Supply on Iraqi Gross Domestic Product from 1990 to 2022 Using ARDL Model - Dorgham Mohammed Abdel Wahab; Hayder Sami Alwan; Maan Abood Ali (Interaction Communication Studies Journal, 2026)
This research interests in investigating a relationship between money supply and gross domestic product , based on official statistics released by Central Statistical Organization through above-mentioned time. These data analyzed using EViews 13 program by using ARDL model, as it is suitable for this sample size and integration properties of variables. The findingss appered positively and statistically significant relationship between monetary supply and GDP in short time. Stationarity of time series was tested using the ADF, indicating stationarity of both money supply and GDP at first difference, explaining both of them are integrated of order one, I(1). Graphical diagram also illustrated overall ascending trend in time series of both variables. However, results of Bounds Test indicated absence of a long-term balance between research variables, as calculated F-statistic (2.19) was smaller than lower bound critical value at 5% significance level. Furthermore, diagnostic examines confirmed the stability of model parameters and absence of autocorrelation and heteroskedasticity problems. Error correction term was negatively and statistically significant, indicating presence of short-term adjustment method.